AI based colorectal disease detection using real-time screening colonoscopy. Issue 2 (20th May 2021) - Jiang, Jiawei; Xie, Qianrong; Cheng, Zhuo; Cai, Jianqiang; Xia, Tian; Yang, Hang; Yang, Bo; Peng, Hui; Bai, Xuesong; Yan, Mingque; Li, Xue; Zhou, Jun; et al.
Abstract: Colonoscopy is an effective tool for early screening of colorectal diseases. However, the application of colonoscopy in distinguishing different intestinal diseases still faces great challenges of efficiency and accuracy. Here we constructed and evaluated a deep convolution neural network (CNN) model based on 117 055 images from 16 004 individuals, which achieved a high accuracy of 0.933 in the validation dataset in identifying patients with polyp, colitis, colorectal cancer (CRC) from normal. The proposed approach was further validated on multi-center real-time colonoscopy videos and images, which achieved accurate diagnostic performance on detecting colorectal diseases with high accuracy and precision to generalize across external validation datasets. The diagnostic performance of the model was further compared to the skilled endoscopists and the novices. In addition, our model has potential in diagnosis of adenomatous polyp and hyperplastic polyp with an area under the receiver operating characteristic curve of 0.975. Our proposed CNN models have potential in assisting clinicians in making clinical decisions with efficiency during application.